The Influence of Collaborative Governance In Improving Preparedness For A Volcanic Eruption (Journal of Namibian Studies : History Politics Culture, 2023)
Disaster is an event that can result in loss of property, life and the environment. One of the disaster that occurred is volcanic disaster. The problems caused by disasters are very complex and require careful and targeted planning. Good collaborative governance in each program is expected to improve preparedness for volcanic eruptions.The purpose of this study was to know how collaborative governance improving preparedness for volcanic eruptions. The research design used in this study was quantitative with cross sectional approach. The sampling technique used is total sampling with total sample of 530 respondents. Collecting data using questionnaire. Data analysis using the Regresi Linear test showed P = 0.001 meaning that there was the influence of a collaborative governance and increased preparedness in the face of volcanic eruptions.The results show that collaborative governance in disaster risk management is mostly good and most of the preparedness in facing volcanic eruptions is in ready condition. Collaborative governance is factor that greatly influence the increase of preparedness for volcanic eruptions.Suggestions for all elements involved in the management of volcanic eruptions are to improve all elements of governance so the program can be implemented properly. Preparedness for volcanic eruptions also needs further improved.